Pelaksanaan Pembinaan Narapidana Residivise di Lembaga Pemasyarakat - Dessi Perdani Yuris Puspita Sari (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2021)
This article aims to answer the problem of how the process of coaching for recidivist prisoners is and to find out what are the obstacles to the implementation of coaching for recidivist prisoners in Correctional Institutions. In this study, the author uses descriptive research, while the approach method uses empirical juridical. The results and conclusions in this study are that the process of fostering recidivist prisoners carried out in prisons is based on Law Number 12 of 1995 concerning Corrections and Government Regulation Number 31 of 1999 concerning Education and Guidance of Correctional Inmates. The convict coaching stage begins with the registration of prisoners and is followed by a coaching process which is divided into 4 (four) stages, while the obstacles faced in fostering recidivists in Correctional Institutions among the very prominent reasons are the facilities and infrastructure of the institution, the number of officers and prisoners is not comparable , the ability of the officers who are lacking, the absence of supervision from superiors and agencies related to the performance of the officers.